A Study of Islamic and Arab Markets' Role in Revitalizing Urban Spaces - Lotfy, Mohamed Yasser; Soliman, Abdullah; Mandour, Alaa (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2015)
Market places have occupied a major role in most cities around the world, being a site for more than just economic interactions, but rather a cultivating agent for social and cultural growth. The Arab and Islamic cities have a proud history of market places, most of the times being the main core of the city, with urban development encompassing it, and till the present day market places are in the heart of most communities. The modern city brought with it a devaluing of the traditional market places, making it a tourist attraction as in the case of